Artha Sebagai Pemoderasi Beragama Dalam Ajaran Agama Hindu - Sukendri, Nengah; Ardana Putra, I Nyoman Nugraha (Jayapangus Press, 2023)
The purpose of life in Hinduism is Moksha which can achieve through the fulfillment of kama (needs), the use of artha (assets), and the path of dharma. This study aims to explore the public's understanding of Artha as a religious moderator, analyze the concept of Artha as a spiritual moderator, and analyze the challenges and strategies of the Hindu community of Mataram City regarding Artha as a religious moderator. Through a qualitative approach by combining primary and secondary data as well as data collection techniques, interviews, observation, and documentation of the community, community leaders, and Hindu community leaders in the city of Mataram. Data analysis using Miles and Huberman analysis. The results of this study indicate that the Hindu community of Mataram City understands religious moderation as a moderate perspective on religion. Artha is meant, in this case, both material and non-material. Will realize This reasonable condition if it has a national commitment, tolerance, and non-violence. Therefore, the Hindu Community of Mataram City already understands what religious moderation means, but it has not been maximized in practice. In addition, the concept of artha has a very close and interrelated relationship with religious moderation. To obtain and use it must always be based on dharma by following the ideas and sources of Hindu teachings, which are also in line with the values ​​contained in Pancasila. The implementation challenges are related to limited human resources, and it is hoped that in the future, they can carry out strategies through religious leaders and community leaders who continue to provide understanding and enlightenment, strengthening the importance of religious moderation.